P172 'It's really just been a learning experience': A qualitative study to explore the experiences of people with chronic obstructive pulmonary disease (COPD) using activity monitors. (11th November 2022) - Wilde, LJ; Clark, C; Percy, C; Ward, G; Wark, PA; Sewell, L
Abstract : Introduction and Objectives: Apps and wearables are increasingly being used by people with Chronic Obstructive Pulmonary Disease (COPD) to help improve levels of physical activity. Physical activity can increase life expectancy, reduce hospital admission, and improve quality of life for people with COPD. Previous research has focussed on the use of activity monitors for monitoring physical activity, often as an objective research measure. However, understanding the experiences of people with COPD using monitoring technology in everyday life could support the development and delivery of effective interventions to increase activity levels. Therefore, this qualitative study aimed to explore the experiences of people with COPD using activity monitors at home in everyday life. Methods: Seven semi-structured face-to-face or telephone interviews were conducted with people with COPD between August 2018 and June 2020. Eligible participants had all used apps and/or wearables (i.e., Fitbit, Garmin, or Apple Watch) to monitor their activity (e.g., steps, distance, heart rate) within the last year. Interviews were analysed using Interpretative Phenomenological Analysis (IPA). Results: Four themes were developed using IPA demonstrating the positive and negative journey of engagement with activity monitors over time: 1) Motivational features to keep monitoring physical activity, 2) The importance of setting achievable goals to manage expectations of activity, 3) Development of knowledge and awareness of activity levels, and 4) Life with the tracker from 'before' to 'now'. Conclusions: This study has provided a detailed insight into how people with COPD use apps and wearables to monitor their physical activity at home in everyday life. Monitoring technology has the potential to widely benefit people with COPD by increasing physical activity and self-management of their health condition. However, further research is needed to understand how healthcare practitioners can support and encourage people with COPD to engage with technology. Understanding how to incorporate technology and utilise activity data collected at home could enable more effective remote delivery of interventions, healthcare, and treatment.